2018
DOI: 10.1007/s12325-018-0781-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity, Neurotransmission and Brain-Related Genes in Major Depression and Bipolar Disorder: Focus on Treatment Outcomes in an Asiatic Sample

Abstract: IntroductionMood disorders are common and disabling disorders. Despite the availability of over 100 psychotropic compounds, only one-third of patients benefit from first-line treatments. Over the past 20 years, many studies have focused on the biological factors modulating disease risk and response to treatments, but with still inconclusive data. In order to improve our current knowledge, in this study, we investigated the role of a set of genes involved in different pathways (neurotransmission, neuroplasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The overlap between eGenes and pGenes from PICS and TORUS fine-mapping was very small, with 3 genes in total. Among them, KTN1 has also been associated with MD ( Dall’Aglio et al, 2021 ) and ESYT2 is involved in neurodevelopmental pathways and may be associated with suicidal behaviour trends in MDD although more research is needed ( Calabrò et al, 2018 ). eGenes from PICS+CLPP were functionally enriched with miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The overlap between eGenes and pGenes from PICS and TORUS fine-mapping was very small, with 3 genes in total. Among them, KTN1 has also been associated with MD ( Dall’Aglio et al, 2021 ) and ESYT2 is involved in neurodevelopmental pathways and may be associated with suicidal behaviour trends in MDD although more research is needed ( Calabrò et al, 2018 ). eGenes from PICS+CLPP were functionally enriched with miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is a stress-sensitive area, and here Homer1 proteins functionally interact with metabotropic mGluR5 glutamate receptors to control glutamate-dependent behaviours. The evidence for the involvement of the Homer1 rs7713917 polymorphism in BD derives from just one study (Benedetti et al, 2018), while other studies showed only a general reduction of Homer1 expression in post-mortem PFC of patients with BD and schizophrenia (Zimmerman et al, 2020) or no association of eight HOMER1 SNPs with BD in an underpowered study (Calabrò et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may contribute to these inconsistent results.SCZ has been linked to genetic and environment factors.HT2A gene was reported to beassociated with more than one mental disorder (obsessive-compulsive disorder, schizophrenia, bipolar disorder and major depressive disorders) [28].The rs643627 within 5-HTR2Agene was also reported to be associated with psychiatric disorder, bipolar disorder and major depressive disorders [19].…”
Section: The Association Between Htr2a Rs643627 Polymorphism and Gendermentioning
confidence: 99%